Quality of life domains relevant to people living with HIV and AIDS who are on antiretroviral therapy in Swaziland - Theresa T. Ntshakala; Thandisizwe R. Mavundla; Bethabile L. Dolamo (AOSIS, 2012)
Quality of life (QOL) domains that are context specific to people living with HIV and AIDS (PLWHA) who are on antiretroviral therapy (ART) in Swaziland are unknown. This presents a problem when research has to be conducted on QOL of PLWHA who are on ART. As a result, this study was conducted to identify, validate and describe domains necessary to assess QOL of PLWHA, who are on ART in Swaziland. A qualitative, explorative, descriptive, and contextual design was used for this study. The first phase dealt with a review of fifty existing QOL definitions and the identification of the common domains amongst them. Findings from this review revealed that the most common domains of QOL are the physiological, psychological, spiritual and socio-economic domains. The second phase was the validation of the above common domains identified from the examined QOL definitions to make them context specific to PLWHA who are on ART in Swaziland. A workshop was used to validate the domains with expert nurses involved in the care of PLWHA in Swaziland. The experts in ART care were trained on ART and had more than a year's experience of working with PLWHA who are on ART. The validation process revealed that the essential context specific domains to consider when assessing QOL of PLWHA who are on ART are, (1) physiological domain, (2) psychological domain, (3) spiritual domain, (4) socio-economic domain, (5) cognitive domain, and (6) environmental domain. The process of validation of the domains was important as two extra domains